The Effect Of Spilitual Ledership, Organizational Culture and Enterpreneurship on Employees Working Motivation and Performance - maskudi, maskudi (Laporan Penelitian dan Pengabdian Masyarakat, 2024)
Abstract This study aims to test the effect of spiritual leadership and organizational culture on job satisfaction and employee performance. Structural equation modelling is applied to analyze data from 170 respondents. The results show spiritual leadership and job satisfaction have a significant effect on job satisfaction as does organizational culture on employee performance. In contrast to expectations, neither spiritual leadership nor organizational culture have effect on employee performance or job satisfaction. Key words: Spiritual leadership, organizational culture, job satisfaction, employee performance